Concerted suppressive effects of carisbamate, an anti-epileptic alkyl-carbamate drug, on voltage-gated Na+ and hyperpolarization-activated cation currents - Hung, Te-Yu; Wu, Sheng-Nan; Huang, Chin-Wei (Frontiers in Cellular Neuroscience, 2023)
Carisbamate (CRS, RWJ-333369) is a new anti-seizure medication. It remains unclear whether and how CRS can perturb the magnitude and/or gating kinetics of membrane ionic currents, despite a few reports demonstrating its ability to suppress voltage-gated Na+ currents. In this study, we observed a set of whole-cell current recordings and found that CRS effectively suppressed the voltage-gated Na+ (INa) and hyperpolarization-activated cation currents (Ih) intrinsically in electrically excitable cells (GH3 cells). The effective IC50 values of CRS for the differential suppression of transient (INa(T)) and late INa (INa(L)) were 56.4 and 11.4 M, respectively. However, CRS strongly decreased the strength (i.e., area) of the nonlinear window component of INa (INa(W)), which was activated by a short ascending ramp voltage (Vramp); the subsequent addition of deltamethrin (DLT, 10 M) counteracted the ability of CRS (100 M, continuous exposure) to suppress INa(W). CRS strikingly decreased the decay time constant of INa(T) evoked during pulse train stimulation; however, the addition of telmisartan (10 M) effectively attenuated the CRS (30 µM, continuous exposure)-mediated decrease in the decay time constant of the current. During continued exposure to deltamethrin (10 M), known to be a pyrethroid insecticide, the addition of CRS resulted in differential suppression of the amplitudes of INa(T) and INa(L). The amplitude of Ih activated by a 2-s membrane hyperpolarization was diminished by CRS in a concentration-dependent manner, with an IC50 value of 38 M. For Ih, CRS altered the steady-state I–V relationship and attenuated the strength of voltage-dependent hysteresis (Hys(V)) activated by an inverted isosceles-triangular Vramp. Moreover, the addition of oxaliplatin effectively reversed the CRS-mediated suppression of Hys(V). The predicted docking interaction between CRS and the hyperpolarization-activated cyclic nucleotide-gated (HCN) channel or between CRS and the hNaV1.7 channel reflects the ability of CRS to bind to amino acid residues in HCN or hNaV1.7 channel via hydrogen bonds and hydrophobic interactions. These findings reveal the propensity of CRS to modify INa(T) and INa(L) differentially and to effectively suppress the magnitude of Ih. INa and Ih are thus potential targets of the actions of CRS in terms of modulating cellular excitability.